Evaluasi Program Kelas Riset di MAN 2 Ponorogo Pada Masa Pandemi COVID-19 - Reny Refitaningsih Peby Ria (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2021)
ABSTRACT This study aims to evaluate the implementatiton of the research class program at MAN 2 Ponorogo. The CIPP model was adopted as the evaluation model in this study. The sources of data information are vice principals of curriculum, vice principals of student, teacher of research, and students. The data in this study were collected through observation, interviews, questionnaires, and documentation. The findings showed that: (1) context, research class programs were very much needed to support the policy of establishing research schools; (2) input, the school had established a research class student selection system, and the provision of infrastructure to support program implementation; (3) the process, the research class service program ran smoothly even-though there were obstacles that hindered the running of the program (4) the implementation of the research class program had been achieved in accordance with the program's achievement criteria. Keywords research class, program evaluation, cipp model